The Influence of Human Resource Planning, Physical Work Environment and Non-Physical Work Environment on Performance Production Employees at PT Perkebunan Nusantara IV Regional I Kebun Bandar Betsy - Dia, Dia; Pohan, Yuli Arnida (CV. Civiliza Publishing, 2025)
This study aims to find out and analyze the partial and simultaneous influence of human resource planning, physical work environment and non-physical work environment on employee performance at PT Perkebunan Nusantara IV Regional I Kebun Bandar Betsy . This type of research uses causal associative research and the research method used in this study is the quantitative method. The population in this study is all production employees of PT Perkebunan Nusantara IV Regional I Kebun Bandar Betsy which totals 62 people. The sampling technique in this study is to use a sampling technique with a nonprobability sampling method with a saturated sample technique where the entire population is used as a sample. With the distribution of the questionnaire, the focus is on all employees of PT Perkebunan Nusantara IV Regional I Kebun Bandar Betsy . The results of the study explained that human resource planning partially had a significant effect on employee performance at PT Perkebunan Nusantara IV Region I. The physical work environment partially affects the performance of employees of PT Perkebunan Nusantara IV Regional I. . The non-physical work environment partially has a negative and insignificant effect on the performance of employees of PT Perkebunan Nusantara IV Region I. HR planning, physical work environment and non-physical work environment simultaneously have a significant effect on the performance of employees of PT Perkebunan Nusantara IV Region I. adjusted R square value of 0.755 can be called the determination coefficient, this means that 0.755 (75.5%) employee performance can be obtained and explained by HR planning, physical work environment and non-physical work environment while the remaining 24.5% is explained by variables outside the model that were not studied